Development of biochar from coconut shell; pyrolisis process / Nur Ariesya Tasneem Azmy - Azmy, Nur Ariesya Tasneem (2023)
Biochar is a high-carbon material. It can be used as a renewable fuel as well as an addition to improve soil quality. Coconut shell waste will cause environmental problem if it is not treated appropriately. The main purpose of this study is to formulate and prepare biochar and to perform the study on pore size and adsorption of methylene blue and water of the prepared biochar. The effect on pore size and adsorption of methylene blue and water at various time (3 hours, 4 hours, 5 hours, 6 hours) at temperature 700℃ were evaluated. Based on the result, pyrolysis process in 6 hours is the best duration for process biochar. After that, for biochar, the physical and chemical properties such as pore size and adsorption of methylene blue and water were being tested. The results showed that long time for pyrolysis process, had higher pore size surface area, and higher adsorption of methylene blue and water as compared to those of short time for pyrolysis process.